Analisis Penggunaan Cangkang Kepiting Bakau Scylla Serrata Sebagai Subtitusi Parsial Semen Terhadap Kuat Tekan Dan Kuat Lentur Beton Dengan Bahan Tambah Superplasticizer - Rahman, Laode Abdul; Syariman, Syahrul; Setiawan, Arman (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Agricultural waste such as crab shells has the potential to pollute the surrounding environment. Crab shells contain calcium carbonate (CaCO3) which will react with calcium hydroxide in cement, forming a solid compound called calcium silicate hydrate (CSH). This research examines the use of mud crab (Scylla Serrata) shell waste as a partial substitute for cement in making concrete, with the addition of a superplasticizer. The percentage of crab shells used is 0%, 10%, and 20%, as well as 2% superplasticizer. The research results showed a decrease in the compressive strength of concrete with crab shell substitution. At 10% substitution, the compressive strength decreased to 23.38 MPa, and at 20% substitution, it decreased to 16.14 MPa. The flexural strength of concrete also decreases, where 10% substitution produces a flexural strength of 3.53 MPa, and 20% substitution produces 1.60 MPa. With the addition of 2% superplasticizer, 10% crab shell substitution showed a compressive strength of 26.87 MPa, higher than normal concrete. However, at 20% substitution, the compressive strength decreased to 18.01 MPa. The flexural strength of concrete with 2% superplasticizer also decreased; 10% substitution shows a flexural strength of 3.87 MPa, higher than normal concrete, while 20% substitution decreases to 2.53 MPa.